Electrophysiological Markers of Chemotherapy-Induced Polyneuropathy - Olga A. Tikhonova; Evgeniia S. Druzhinina; Dmitry S. Druzhinin (Анналы клинической и экспериментальной неврологии)
Introduction. Electrophysiological testing is the gold standard for diagnosing polyneuropathy. However, its use in oncology practice for patients with chemotherapy-induced polyneuropathy (CIPN) remains limited and the value of its findings is not fully understood.